Microstructural characterization of carbon steels using ultrasonic velocity measurements - Vera Lúcia de Araújo Freitas (2009)
Non-destructive techniques are suitable alternatives for analysis and microstructural characterization of steels phases. Based on this, this work aims to analyze the behavior of longitudinal and transverse ultrasonic velocities in three different types of AISI steels: 1006, 1080 and quenched 1045. These materials were selected due to their distinct microstructures: ferrite, pearlite and martensite, respectively. By measuring sound velocities for both longitudinal and transversal waves, the reference values were obtained for each steels phase. The sound velocity in martensite is lower than the one in pearlite, and this one is lower than the sound velocity in ferrite. The differences in the values of the sound velocity arise primarily from dissimilarities in the values of the phases elastic modulus which are affected by the degree of lattice distortion and misorientation. Thus, sound velocity measurements can be successfully used as a non-destructive technique to perform steels microstructural characterization. Additionally to ultrasonic testing, the microstructures were characterized by metallography and hardness testing.